Nigral and ventral tegmental area lesioning induces testicular and sperm morphological abnormalities in a rotenone model of Parkinson’s disease (2020)
Although sexual health is affected by Parkinson’s disease (PD), the effect on testicular health and/or sperm quality is not well discussed. After 21 days of rotenone lesioning, we observed dopaminergic neuronal degeneration in the substantia nigra and hypothalamus. There were minimal SPACA-1-expressing epididymal spermatozoa with morphological abnormalities, scanty luminal spermatozoa and reduced testicular spermatids and post-meiotic germ cells indicating hypospermatogenesis. Occludin-expressing sertoli cells were dispersed over a wide area indicating compromised blood-testes barrier. Activated caspase-3 expression was intense while immunoreactivity of spermatogenic-enhancing SRY and GADD45 g was weak. Although serum follicle stimulating hormone level was not affected, the lesion was associated with reduced serum testosterone level, testicular oxidative damage and inhibition of acetylcholinesterase activity, even when rotenone was not detected in the testes. Together, dopaminergic lesions may mediate testicular and sperm abnormalities via the brain-hypothalamic- testicular circuit independent of the pituitary, thereby establishing a causal link between Parkinsonism and reproductive dysfunction.